A Checklist to Assess Adequacy of Vitamin D Intake. Issue 3 (July 2020) - Drummond, James E.; Kraft, Diane
Abstract : Few foods are natural sources of vitamin D in the American diet. A Vitamin D Checklist (VDC) containing 11 food groupings that represent the major sources of the vitamin was developed to estimate vitamin D intake adequacy. Undergraduate students (N = 82, 25 males and 57 females) completed a 3-day food record (FR) and analyzed them with the USDA Supertracker nutrition analysis program, which generated their daily average vitamin D intake as a % of their vitamin D RDA (%D-RDA). Subjects also completed a VDC for the same 3-day FR period. FR %D-RDA correlated with higher VDC recall of consuming either milk ( P ⩽ .001), vitamin D–fortified cereal ( P ⩽ .001), or American cheese ( P = .02). The greater the number of VDC food groupings consumed, the higher the estimated FR %D-RDA. We concluded that the VDC may have applications for use as a tool for a quick assessment of vitamin D intake in patient settings.